Recreating composition, structure, functionalities of tissues at nanoscale for regenerative medicine - ALARÇİN, EMİNE (FUTURE MEDICINE LTD, 2016)
Nanotechnology offers significant potential in regenerative medicine, specifically with the ability to mimic tissue architecture at the nanoscale. In this perspective, we highlight key achievements in the nanotechnology field for successfully mimicking the composition and structure of different tissues, and the development of bio-inspired nanotechnologies and functional nanomaterials to improve tissue regeneration. Numerous nanomaterials fabricated by electrospinning, nanolithography and self-assembly have been successfully applied to regenerate bone, cartilage, muscle, blood vessel, heart and bladder tissue. We also discuss nanotechnology-based regenerative medicine products in the clinic for tissue engineering applications, although so far most of them are focused on bone implants and fillers. We believe that recent advances in nanotechnologies will enable new applications for tissue regeneration in the near future.
Keywords: biomimetic; drug delivery; FDA-approved products; nanomaterial; nanostructure; nanotechnology; regenerative medicine; tissue regeneration; MESENCHYMAL STEM-CELLS; EXTRACELLULAR-MATRIX; CARTILAGE REGENERATION; IN-VIVO; NANOFIBERS; SCAFFOLDS; COLLAGEN; DIFFERENTIATION; NANOSTRUCTURES; NANOTECHNOLOGY